Jaka pedagogika krytyczna jest (nie)możliwa w Polsce i dlaczego? (Esej metakrytyczny z Henrym A. Giroux w tle) - Witkowski, Lech (Chowanna, 2020)
The text undertakes the problematics situated between modernity and tradition regarding the reception of H.A. Giroux’s works in Poland, in a view of furthering the study of pedagogy and educational praxis. First, the author outlines the beginnings of openness towards critical pedagogy. What is underscored here is the 1980s’ main inspiration drawn from the resistance paradigm. Then, the author proceeds to the current state of Giroux’s reception in Poland. He illustrates differences among particular examples and levels of the said reception of Giroux’s pedagogy and of the scholar’s theoretical background. The emphasized disputes pertain especially to transcending metaphysics and relativism as a challenge faced by hermeneutical criticism and critical hermeneutics. Additionally, the “critical” horizon of the main handbook of pedagogy used in Polish universities is discussed. The author point to the wasteful efforts at instigating the breakthrough in the reception of critical pedagogy and he exemplifies them by an instance of misbegotten analysis of the allegedly delayed critical pedagogy of work. As a particularly positive example the author presents a new effort at developing critical hermeneutics (and radical praxis) for pedagogy by Andrzej Wierciński. In the concluding part written “in lieu of conclusions,” four lists of critical problems’ dislocations are provided; the problems are both convergent and related to one another, thereby redefining current research objectives and pertain to practical applications in educational praxis.